Dose calculations and measurments in radiotherapy with the use automaticly wedge filter - Popielarz, Magdalena; Piotrowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2000)
The aim of the study was to determine an algorithm enabling to obtain an assigned inclination angle of isodoses in Saturn 43F linear accelerator with the use of an automatic wedge filter. It was assumed that in an assigned inclination angle of a reference isodose can be obtained after combining absorbed doses during irradiation with an open field and a field with a constant 60 o wedge. In order to find relations between isodoses angles and an irradiating time the doses in a plexiglass phantom were measured in referring depths (5 cm for irradiating energy X 6 MV and 10 cm for X 15 MV and X 25 MV) down the wedge axis for and open field and later for a field of 60 o wedge. The differences were calculated according to their respective depth differences, which enabled to determine an inclination angle of isodoses down the wedge to an isodose for an open field.